Alyssum homolocarpum seed oil (AHSO), containing natural alpha linolenic acid, stearic acid, myristic acid and β-sitosterol, increases proliferation and differentiation of neural stem cells in vitro - Reza Mahmoudi; Majid Ghareghani; Kazem Zibara; Maryam Tajali Ardakani; Yahya Jand; Hassan Azari; Jafar Nikbakht; Amir Ghanbari (BMC, 2019)
Abstract Background Embryonic neural stem cells (eNSCs) are immature precursors of the central nervous system (CNS), with self-renewal and multipotential differentiation capacities. These are regulated by endogenous and exogenous factors such as alpha-linolenic acid (ALA), a plant-based essential omega-3 polyunsaturated fatty acid. Methods In this study, we investigated the effects of various concentrations of Alyssum homolocarpum seed oil (AHSO), containing natural ALA, stearic acid (SA), myristic acid (MA), and β-sitosterol, on proliferation and differentiation of eNSCs, in comparison to controls and to synthetic pure ALA. Results Treatment with natural AHSO (25 to 75 μM), similar to synthetic ALA, caused a significant ~ 2-fold increase in eNCSs viability, in comparison to controls. To confirm this proliferative activity, treatment of NSCs with 50 or 75 μM AHSO resulted in a significant increase in mRNA levels of notch1, hes-1 and Ki-67and NICD protein expression, in comparison to controls. Moreover, AHSO administration significantly increased the differentiation of eNSCs toward astrocytes (GFAP+) and oligodendrocytes (MBP+) in a dose dependent manner and was more potent than ALA, at similar concentrations, in comparison to controls. Indeed, only high concentrations of 100 μM AHSO, but not ALA, caused a significant increase in the frequency of neurons (β-III Tubulin+). Conclusion Our data demonstrated that AHSO, a rich source of ALA containing also other beneficial fatty acids, increased the proliferation and stimulated the differentiation of eNSCs. We suggest that AHSO's effects are caused by β-sitosterol, SA and MA, present within this oil. AHSO could be used in diet to prevent neurodevelopmental syndromes, cognitive decline during aging, and various psychiatric disorders.